Abstracts of the 11th Nordic Music Therapy Conference 2024: Let’s face the music: Book of Abstracts - Ochsner Ridder, Hanne Mette; Lindahl Jacobsen, Stine (Tidsskriftet Dansk Musikterapi, 2024)
Book of Abstracts